2023
DOI: 10.3390/ijms24098323
|View full text |Cite
|
Sign up to set email alerts
|

Light-Dependent Regulatory Interactions between the Redox System and miRNAs and Their Biochemical and Physiological Effects in Plants

Abstract: Light intensity and spectrum play a major role in the regulation of the growth, development, and stress response of plants. Changes in the light conditions affect the formation of reactive oxygen species, the activity of the antioxidants, and, consequently, the redox environment in the plant tissues. Many metabolic processes, thus the biogenesis and function of miRNAs, are redox-responsive. The miRNAs, in turn, can modulate various components of the redox system, and this process is also associated with the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…This change results in greater induction of miR395 and smaller expression of ATP sulfurylase4 ( APS4 ) during sulphur starvation than under optimal sulphur supply in far‐red light. The mediator role of the redox system is also supported by the identification of several redox‐responsive miRNAs (Cimini et al 2019; Gulyás et al 2023).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This change results in greater induction of miR395 and smaller expression of ATP sulfurylase4 ( APS4 ) during sulphur starvation than under optimal sulphur supply in far‐red light. The mediator role of the redox system is also supported by the identification of several redox‐responsive miRNAs (Cimini et al 2019; Gulyás et al 2023).…”
Section: Discussionmentioning
confidence: 96%
“…How to cite this article: Székely, A., Gulyás, Z., Balogh, E., Payet, R., Dalmay, T., Kocsy, G. et al (2023)…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…All five research articles demonstrated the transcriptional regulation of the metabolism by light and two of them [ 2 , 4 ] showed the involvement of the redox system in this process. Thus, the review of Gulyás et al [ 6 ] about the light-dependent interactions between the redox system and miRNAs can be related to all of them since miRNAs can regulate the transcription of their target genes. Although none of the research articles presented the control of metabolism by miRNAs, this research field is worthy for future studies based on the review.…”
mentioning
confidence: 99%